2016
DOI: 10.21548/34-1-1087
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pulp on the Chemical Profile of Mango Wine

Abstract: The aim of this study was to assess the effect of mango pulp inclusion (which mimicked the maceration step in grape wine fermentation) on the fermentation dynamics and chemical profile of mango wine, especially the volatiles. The growth of Saccharomyces cerevisiae MERIT.ferm was slower in the mango juice with pulp (uncentrifuged juice), with a corresponding slower reduction in °Brix, relative to the juice without pulp (centrifuged juice). The utilisation of glucose, fructose and sucrose was similar in both unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
4
1
Order By: Relevance
“…These results are higher than those reported in other studies on pomegranate (between 8.30% and 9.05% v/v) (Andreu-Sevilla et.al 2013) and other fruit wines, such as marula (5.5% v/v) (Hiwilepo-van Hal et al, 2013) or mango (between 6.50% and 7.99% v/v) (Li et al, 2013;Reddy and Reddy, 2005).…”
Section: Ethanol and Glycerol Productioncontrasting
confidence: 59%
See 1 more Smart Citation
“…These results are higher than those reported in other studies on pomegranate (between 8.30% and 9.05% v/v) (Andreu-Sevilla et.al 2013) and other fruit wines, such as marula (5.5% v/v) (Hiwilepo-van Hal et al, 2013) or mango (between 6.50% and 7.99% v/v) (Li et al, 2013;Reddy and Reddy, 2005).…”
Section: Ethanol and Glycerol Productioncontrasting
confidence: 59%
“…Fermented beverages from fruit, or so-called "fruit wines" are made from various types of fruit: strawberry (Hidalgo et al, 2013), marula (Hiwilepo-van Hal et al, 2013), sand pear (Joshi et al, 2014), apple (Herrero et al, 1999), papaya (Lee et al, 2012), mango (Li et al, 2011(Li et al, , 2013, orange (Fernández-Pachón et al, 2014;Kelebek et al, 2009) and pomegranate (Mena et al, 2012;Zhuang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that higher alcohols can be detrimental to wine aroma at levels above 350 mg L −1 (Swiegers et al ., ). The reason for this aberrant production of isoamyl alcohol is not clear, but it may relate to the presence of L‐leucine (Fowomola, ; Li et al ., ) and/or the redox imbalance caused by the hypersomotic stress. Isoamyl alcohol can be synthesised from sugar metabolism via pyruvate, which can be converted into leucine (Kohlhaw, ; Yuan et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, odorless volatile precursors exist in fruit with a large amount [9]. Glycosidase can cleave the sugar moieties from bound volatiles to release free volatiles that can contribute to the overall aroma of wine [9,11,12,13]. For example, terpene alcohols are the major volatile aglycones released from their precursors by glycosidase in grape wine, and these aromatic compounds can improve the floral and fruity notes of the overall aroma of grape wine [9,11,12,13].…”
Section: Introductionmentioning
confidence: 99%